2008
DOI: 10.1007/s00134-008-1200-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced fluid management with continuous venovenous hemofiltration in pediatric respiratory failure patients receiving extracorporeal membrane oxygenation support

Abstract: Use of CVVH in ECMO was associated with improved fluid balance and caloric intake and less diuretics than in case-matched ECMO controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 22 publications
0
84
0
2
Order By: Relevance
“…Data from the present study 1) provide a current estimate of CHX contamination in commercially available IV bags and EC circuits and 2) clearly indicate that the effects of 210 g/l IV CHX (a concentration that conservatively approximates clinical exposure for EC patients) mirror the cardiovascular morbidities associated with EC: bradycardia/dysrhythmia (1,4,5,19,33,38), depressed ventricular contractility (1,2,4,5,8,11,18,19,24,33,38,39,41), low cardiac output (7,11,14,28,31), high systemic and pulmonary vascular resistance (7, 13, 18, 29 -31), hypotension/labile blood pressure (2,7,21), pulmonary hypertension (7, 29 -31), impaired neurological (baroreflex) function (3,5,34,38,39), and edema formation (20,32,39).…”
Section: Discussionmentioning
confidence: 99%
“…Data from the present study 1) provide a current estimate of CHX contamination in commercially available IV bags and EC circuits and 2) clearly indicate that the effects of 210 g/l IV CHX (a concentration that conservatively approximates clinical exposure for EC patients) mirror the cardiovascular morbidities associated with EC: bradycardia/dysrhythmia (1,4,5,19,33,38), depressed ventricular contractility (1,2,4,5,8,11,18,19,24,33,38,39,41), low cardiac output (7,11,14,28,31), high systemic and pulmonary vascular resistance (7, 13, 18, 29 -31), hypotension/labile blood pressure (2,7,21), pulmonary hypertension (7, 29 -31), impaired neurological (baroreflex) function (3,5,34,38,39), and edema formation (20,32,39).…”
Section: Discussionmentioning
confidence: 99%
“…[15] Many medical centers offer continuous RRT as the most manageable and effective method. [16] We chose CVVHF, which influences various aspects of the pathogenesis of MODS, inhibits its development and progression, and helps eliminate the medium molecular weight substances, thereby contributing to a decrease in inflammatory cascade activity. [17] In addition, the use of high volumes of replacement liquids (more than 30-35 mL/kg/h) can be of great importance for enhancing lymphatic transport between the intercellular space, tissues and blood and for reducing the activity of the inflammatory cascade.…”
Section: Cvvhf In Conjunction With Ecmo In Children With Critical Heamentioning
confidence: 99%
“…5). In a study on fluid management with continuous venovenous hemofiltration in pediatric patients receiving ECMO support, Hoover et al [79] showed that the use of continuous venovenous hemofiltration in ECMO was associated with improved fluid balance, increased caloric intake and less diuretics administration, compared with case-matched ECMO controls. However, unlike the venovenous ECCO2R machines, potential implications of attaching continuous RRT to ECMO circuit should be carefully considered and is best done at centers specialized in these techniques.…”
Section: Pulmonary/renal Support – Mostmentioning
confidence: 99%